Macrophage–Microbe Interactions: Lessons from the Zebrafish Model - Yoshida, Nagisa; Frickel, Eva-Maria; Mostowy, Serge (Frontiers in Immunology, 2017)
Macrophages provide front line defence against infections. The study of macrophage-microbe interplay is thus crucial for understanding pathogenesis and infection control. Zebrafish (Danio rerio) larvae provide a unique platform to study macrophage-microbe interactions in vivo, from the level of the single cell to the whole organism. Studies using zebrafish allow non-invasive, real-time visualisation of macrophage recruitment and phagocytosis. Furthermore, the chemical and genetic tractability of zebrafish has been central to decipher the complex role of macrophages during infection. Here, we discuss the latest developments using zebrafish models of bacterial and fungal infection. We also review novel aspects of macrophage biology revealed by zebrafish which can potentiate development of new therapeutic strategies for humans.